Delirium in Covid-19 Patients: Literature Review - Ady Fitra Saragih (HM Publisher, 2022)
Many countries throughout the world have experienced an extraordinary health crisis as a result of the coronavirus-2 infection (SARS-CoV-2). The coronavirus 2019 (COVID-19) is particularly concerning in older adults, for whom multimorbidity and vulnerability that underpins the risk of negative consequences following the illness. Individuals who are diagnosed with the coronavirus disease 2019 have breathing and digestive issues. The SARS-CoV-2 virus has the potential to affect central nervous system (CNS) which results in delirium and respiratory failure. Delirium is a severe brain dysfunction that can be potentially lethal and is characterized by inattention and mental changes that are fluctuating.